Community and hospital acquired Clostridium difficile in South Australia – ribotyping of isolates and a comparison of laboratory detection methods. (21st November 2014) - Wilson, R.; Beerbaum, P.; Giglio, S.
Abstract A total of 274 samples were screened for toxigenic Clostridium difficile using a combination of several commercially available assays, and positive isolates ribotyped. A two‐step algorithm assisted in demonstrating an increased prevalence of C. difficile infection in South Australia of 9·8%, most of which were ribotypes 014 and 052. A glutamate dehydrogenase assay followed by the detection of genes associated with toxin production was the most sensitive and specific algorithm for screening for toxigenic C. difficile. Significance and Impact of the Study Rapid and accurate detection of toxigenic Clostridium difficile is important for the diagnosis of C. difficile colitis and the management of patients in healthcare institutions to minimize the spread of disease. A critical review of currently available commercial methods supports a recommendation for a 2‐step algorithm that is relatively inexpensive and amenable to the routine pathology laboratory. It is anticipated that the detection of C. difficile will increase with improved detection methods, and the ribotype prevalence presented in this manuscript will be useful for any current and future source tracking purposes.